IMPROVEMENT IN CONCEPTION RATE BY GnRH OR hCG ADMINISTRATION ON DAY 5 POST-AI IN NON-INFECTIOUS REPEAT BREEDER COWS - ANBHULE, R S; SAWALE, A G; MARKANDEYA, N M; KUMAWAT, B L; KADAM, P D; LAWANGE, S R (The Indian Journal of Animal Reproduction, 2022)
Thirty-six non-infectious repeat breeder cows were selected on the basis of typical fern pattern, negative white side test, normal pH of cervical mucus and <4% polymorphonuclear (PMN) cell count in endometrial content. Selected animals were randomly distributed in three groups containing twelve animals each. Group-I and Group- II were treated with inj. GnRH @ 10 mcg and inj. hCG @ 2000 IU by intramuscular route, respectively on day 5 post-AI, whereas group-III served as controls. Conception rates in group I, II and III was recorded as 58.3, 66.7 and 25.0%, respectively. Thus, hCG treatment on day 5 post-AI improved conception rate in non-infectious repeat breeder cows.